Efficient Gene Silencing by Self-Assembled Complexes of siRNA and Symmetrical Fatty Acid Amides of Spermine - Charareh Pourzand; Ian S. Blagbrough; Abdelkader A. Metwally (MDPI AG, 2011)
Gene silencing by siRNA (synthetic dsRNA of 21-25 nucleotides) is a well established biological tool in gene expression studies and has a promising therapeutic potential for difficult-to-treat diseases. Five fatty acids of various chain length and oxidation state (C12:0, C18:0, C18:1, C18:2, C22:1) were conjugated to the naturally occurring polyamine, spermine, and evaluated for siRNA delivery and gene knock-down. siRNA delivery could not be related directly to gene silencing efficiency as N4,N9-dierucoyl spermine resulted in higher siRNA delivery compared to N4,N9-dioleoyl spermine. GFP silencing in HeLa cells showed that the unsaturated fatty acid amides are more efficient than saturated fatty acid amides, with N4,N9-dioleoyl spermine resulting in the most efficient gene silencing in the presence of serum. The alamarBlue cell viability assay showed that fatty acid amides of spermine have good viability (75%-85% compared to control) except N4,N9-dilauroyl spermine which resulted in low cell viability. These results prove that unsaturated fatty acid amides of spermine are efficient, non-toxic, non-viral vectors for siRNA mediated gene silencing.